Effects of Spirulina platensis Addition on Growth of Lactobacillus plantarum Dad 13 and Streptococcus thermophilus Dad 11 in Fermented Milk and Physicochemical Characteristics of the Product - Luwidharto, Joshua Christmas Natanael; Rahayu, Endang S.; Suroto, Dian Anggraini; Wikandari, Rachma; Ulfah, Ardhika; Utami, Tyas (Applied Food Biotechnology, 2022)
Abstract Background and Objective: Spirulina platensis includes excellent bioactive compounds, which provide health-promoting effects. However, use of Spirulina platensis in foods includes limitations due to its unpleasant flavor and taste for some people. Fermented milk products include typical taste and flavor of fresh acid and can be combined with Spirulina platensis. Probiotics of Lactobacillus plantarum Dad 13 and Streptococcus thermophilus Dad 11 isolated from traditional buffalo milks can be used as starter culture strains for the fermented milks. This study investigated lactic acid bacterial growth, acid production and physicochemical characteristics of the fermented milks with Spirulina platensis. Material and Methods: Milk fermentation was carried out using addition of various concentrations (0.15, 0.3, 0.45 and 0.6%) of Spirulina platensis powder and then microbial cell growth, acid production and antioxidant activity were investigated. Fermented milks with selected concentrations of Spirulina platensis were assessed within 24 h of fermentation at 37 °C using single and mixed cultures to study various aspects of cell growth, acid production, viscosity, water holding capacity and color. Results and Conclusion: Increases of Spirulina platensis concentrations in fermented milks increased the microbial cell growth, acid production and antioxidant activity. During milk fermentation by adding 0.3% of Spirulina platensis, cells propagated and total lactic acid bacteria and probiotic cell counts reached to respectively 8.73-9.19 and 8.92 log CFU ml-1 after 24 h. The titratable acidity reached to 1.08% and pH decreased to 4.41. Viscosity increased significantly after 12 h of fermentation, compared to the controls. Fermented milks with Spirulina platensis addition by Lactobacillus plantarum Dad 13 and Streptococcus thermophilus Dad 11 cultures can be developed as alternative functional fermented milk products. Conflict of interest: The authors declare no conflict of interest.